PERANCANGAN STATION ID RTV - Henry Wijaya; Agung Eko Budiwaspada Eko Budiwaspada; Agus Nugroho Ujianto (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2019)
AbstractIn the era of a very limited television industry, television stations need a strategy to seize a selective audience in accordance with the target audience to reach the various audience structures in the community. Rajawali Television as a television company that was established in 2014 and has been airing for 3 years, until now Rajawali has reached the fifth position in Nielsen share rating. In reaching the highest position and able to survive is not easy, a television requires a reminder of identity to the target audience known as station identity. Problems that occur until now RTV has not had id station that aired and aired as a step to maintain and increase sales of this television company. The design of a station identity also requires deep thinking in order to create a station identity that is able to answer the problem. Designing the appropriate station identity, requires several platforms as a reference in the design tailored to the needs. Positioning and differentiation are the foundations used in designing this work, the selection of the two foundations has been adapted to the needs of RTV through the data already obtained. The foundation is applied with appropriate design methods in designing station identity, MDLC (Multimedia Development Life Cycle) becomes an option in designing RTV station identity. The resulting station identity will be distributed to several output media as needed, so that more can be maximized its useAbstrakPada era industi televisi yang sangat ketat menyebabkan stasiun televisi membutuhkan strategi merebut penonton yang selektif sesuai dengan target audiens demi menjangkau struktur-struktur penonton yang beragam dalam masyarakat. Rajawali Televisi sebagai sebuah perusahaan televisi yang berdiri pada tahun 2014 dan telah mengudara selama 3 tahun, hingga saat ini Rajawali telah mencapai posisi ke-6 dalam share rating Nielsen. Dalam mencapai posisi tertinggi dan mampu bertahan tidaklah mudah, sebuah televisi memerlukan pengingat identitas kepada target audiens yang dikenal sebagai station identity. Permasalahan yang terjadi hingga saat ini RTV belum memiliki stasiun id yang tayang dan mengudara sebagai langkah menjaga dan meningkatkan penjualan perusahaan televisi ini. Perancangan sebuah station identity juga memerlukan pemikiran yang dalam demi menciptakan sebuah station identity yang mampu menjawab permasalahan tersebut. Merancang station identity yang tepat guna, memerlukan beberapa landasan sebagai acuan dalam perancangan yang disesuaikan dengan kebutuhan. Positioning dan diferensiasi merupakan landasan yang digunakan dalam merancang karya ini, pemilihan dua landasan tersebut telah disesuaikan dengan kebutuhan RTV melalui data yang telah didapat. Landasan tersebut diaplikasikan dengan metode perancangan yang sesuai dalam merancang station identity, MDLC (Multimedia Development Life Cycle) menjadi pilihan dalam merancang station identity RTV. Adapun station identity yang dihasilkan akan didistribusikan kepada beberapa output media sesuai kebutuhan, sehingga semakin dapat dimaksimalkan penggunaannya.